Urogenital chlamydia infection in women: patient management tactics according to present-day foreign and Russian recommendations - A. A. Khryanin (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
The article present data on current approaches to laboratory diagnostics and treatment of urogenital chlamydia infection in women. According to Russian and foreign guidelines, azithromycin, josamycin and doxycycline monohydrate belong to the most efficient antimicrobial drugs for the treatment of urogenital chlamydia infection in non-pregnant women. As for the treatment of pregnant patients suffering from this pathology, azithromycin and josamycin are the most optimal drugs in terms of safety and treatment efficacy according to both Russian and foreign guidelines.